INTEGRATED MANAGEMENT OF ANTHRACNOSE OF CHILLI CAUSED BY COLLETOTRICHUM CAPSICI IN WEST BENGAL CONDITION - SALMA BEGUM; RUPERT ANAND YUMLEMBAM; TANYA R. MARAK; P. S. NATH (The Bioscan, 2015)
Different botanicals, fungicides and bioagents were evaluated in vitro and field condition against Colletotrichum capsici. Amongst fungicides it was found that at 150 ìg/ml concentration 100% inhibition in mycelial growth was recorded in Tebuconazole, Mancozeb and Trifloxystrobin + Tebuconazole and minimum inhibition in mycelial growth was recorded in Carbendazim(6.71%). Two isolates each of three bioagentsviz., Trichoderma harzianum, T. viride and Pseudomonas fluorescens were evaluated for their antagonistic properties against C. capsici. T. harzianum isolate Th-2 was found most effective giving 77.78% inhibition on the mycelial growth followed by T. harzianum isolate Th-1 inhibiting 74.00%. Among four botanical oils Garlic, Neem, Polyalthia and Citronella were tested for their in vitro efficacy against C. capsici at concentrations of 0.05%, 0.1% and 0.2%. Garlic oil at all concentrations and neem oil at 0.1% gave cent per cent inhibition of mycelial growth of the fungus followed by Polyalthia at 0.20% (84.45%). Under field condition, significant minimum disease severity of 4.85% was found in plot receiving seed treatment with garlic oil @ 0.5 ml/kg seed followed by three sprays of Trifloxystrobin+Tebuconazole (50%) @1g/litre water.